2015
DOI: 10.4238/2015.august.14.26
|View full text |Cite
|
Sign up to set email alerts
|

Adaptability and stability of soybean genotypes in off-season cultivation

Abstract: ABSTRACT. The oil and protein contents of soybean grains are important quantitative traits for use in breeding. However, few breeding programs perform selection based on these traits in different environments. This study assessed the adaptability and stability of 14 elite early soybean breeding lines in off-season cultivation with respect to yield, and oil and protein contents. A range of statistical methods was applied and these analyses indicated that for off-season cultivation, the lines UFUS 5 and UFUS 10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 18 publications
(29 reference statements)
1
12
0
2
Order By: Relevance
“…Sci., Bom Jesus, v.9, n.2, p.226-234, Apr./Jun. 2018 between genotype and environment (G x E), which makes the selection or recommendation of genotypes for cultivation in different environments difficult (Batista et al, 2015;Marques et al, 2011). Therefore, to enhance the ability to identify superior genotypes and study the G x E interaction, it is necessary to evaluate genotypes in different environments to minimize the effect of environment on the expression of the phenotype (Sousa et al, 2015;Malosetti et al, 2013;Meotti et al, 2012).…”
Section: Soybean Genetic Breeding Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…Sci., Bom Jesus, v.9, n.2, p.226-234, Apr./Jun. 2018 between genotype and environment (G x E), which makes the selection or recommendation of genotypes for cultivation in different environments difficult (Batista et al, 2015;Marques et al, 2011). Therefore, to enhance the ability to identify superior genotypes and study the G x E interaction, it is necessary to evaluate genotypes in different environments to minimize the effect of environment on the expression of the phenotype (Sousa et al, 2015;Malosetti et al, 2013;Meotti et al, 2012).…”
Section: Soybean Genetic Breeding Programsmentioning
confidence: 99%
“…One of the alternatives to mitigate the influence of the G x E interaction is the recommendation of genotypes with wide adaptability and good stability (Barros et al, 2010). In this context, various methods can be used to evaluate the performance of soybean genotypes and their interaction with the environment aiming at direct selection of the most productive, adapted and stable genotypes for the cultivation in regions (Batista et al, 2015).…”
Section: Soybean Genetic Breeding Programsmentioning
confidence: 99%
“…Soybean breeding programs in Brazil aim at mainly increasing oil and protein content and grain yield in order to ensure competitiveness in the world market (Batista et al, 2015). This has been achieved through continuous genetic improvement which has contributed to the development of soybean cultivars with high yield and adapted to the different environments of Brazilian (Lima et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, some of the studies already carried out, comparing both, have demonstrated differences in agronomic performance (Fonseca et al, 2013;Lima et al, 2008;Lima et al, 2015). The soybean agronomic performance is greatly influenced by the interaction genotype x environment, which makes difficult the identification of adapted and stable genotypes for the different growing regions (Batista et al, 2015;Branquinho et al, 2014). So, to recommend new cultivars, regional studies aimed at minimizing the environmental effects of developing cultivars are always needed (Azevedo et al, 2015;Gomez et al, 2014).…”
Section: Introductionmentioning
confidence: 99%